Surrogacy Market in India: A Critical Analysis - Trika, Akash; Talukdar, Rubi (International Journal of Psychosocial Rehabilitation, 2025)
There is Jewish proverb states that God could not be everywhere so he made mothers. Over a couple of centuries the desire to beget a child for an infertile couple was being satisfied by adoption. But modern sciences has provided new opportunities or options we can say to overcome adoption, that’s surrogacy which has resulted as a boon for those childless couples who want their own child. Surrogacy is a practice whereby a woman agrees to become pregnant by implanted embryo or medically inseminated sperm and bear a child for another person or persons, to whom she intends to transfer the child’s care at, or shortly after, birth and in return receives the compensation for carrying and delivering the child. The Paper is centred on “Surrogacy Market in India”. The paper talks about the history of surrogacy, various moral and ethical issues, judicial response and law governing surrogacy in India.